Міжфазовий розподіл аліфатичних амінів у міцелярно-екстракційній системі при температурі помутніння - Куліченко, С.А.; Дорощук, В.О.; Лелюшок, С.О. (Видавничий дім "Академперіодика" НАН України, 2007)
The influence of the general hydrophobicity of aliphatic amines on the distribution between water and surfactant-rich phases at the cloud point temperature is investigated. The possibility of the separation of amines into two groups depending on their hydrophobicity is shown. The influence of the concentration of a substrate and a non-ionic surfactant on the efficiency of the micellar extraction of amines is investigated. The solvation free energy of aliphatic amines and their molecular fragments is calculated.